2007
DOI: 10.1021/ci600462d
|View full text |Cite
|
Sign up to set email alerts
|

QSPR Study of Critical Micelle Concentration of Anionic Surfactants Using Computational Molecular Descriptors

Abstract: A data set of 181 diverse anionic surfactants has been investigated to relate the logarithm of critical micelle concentration (cmc) to the molecular structure using Comprehensive Descriptors for Structural and Statistical Analysis (CODESSA Pro) software. A fragment approach provided superior quantitative structure-property relationship (QSPR) models in terms of statistical characteristics and predictive ability. The regression equations provided insight into the structural features of surfactants that influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Authors also identified the octanolwater partition coefficient and the dipole moment as suitable measures of the cmc. Finally, the model used was as follows: [53] investigate a data set of 119 diverse anionic surfactants to relate the logarithm of critical micelle concentration (cmc) to the molecular structure using Comprehensive Descriptors for Structural and Statistical Analysis (CODESSA Pro) software. The regression equation obtained contained variables that include features of both hydrophobic and hydrophilic fragments of the surfactant: In this equation the t-sum-Kier & Hall index of 0th order is the sum of the Kier & Hall index of zeroth order over all hydrophobic tails; the total dipole of the molecule is the AM1 calculated total dipole moment of the molecule; and the h-sum relative number of carbon atoms is the sum of the relative number of carbon atoms over all hydrophilic heads.…”
Section: Quantitative Structure Activity Rela-tionship (Qsar) Studiesmentioning
confidence: 99%
“…Authors also identified the octanolwater partition coefficient and the dipole moment as suitable measures of the cmc. Finally, the model used was as follows: [53] investigate a data set of 119 diverse anionic surfactants to relate the logarithm of critical micelle concentration (cmc) to the molecular structure using Comprehensive Descriptors for Structural and Statistical Analysis (CODESSA Pro) software. The regression equation obtained contained variables that include features of both hydrophobic and hydrophilic fragments of the surfactant: In this equation the t-sum-Kier & Hall index of 0th order is the sum of the Kier & Hall index of zeroth order over all hydrophobic tails; the total dipole of the molecule is the AM1 calculated total dipole moment of the molecule; and the h-sum relative number of carbon atoms is the sum of the relative number of carbon atoms over all hydrophilic heads.…”
Section: Quantitative Structure Activity Rela-tionship (Qsar) Studiesmentioning
confidence: 99%
“…Both of these QSPR models were obtained using MLR approach over a set of descriptors based on molecular topology and constitution. Apart from the work of Anoune et al [91], QSPR models intended to the CMC prediction were trained over specific chemical families that are: nonionic [89,[92][93][94][95][96][97][98], cationic [99][100][101], and anionic [90,94,[102][103][104][105][106][107] surfactants. Table 1 presents statistical coefficients of QSPR models listed in the literature.…”
Section: Cmc Predictionmentioning
confidence: 99%
“…This table shows that most of these models have been developed using MLR and we can remark that the size of the database varied from few tens to less than two hundred compounds. Katritzky [96] and Katritzky et al [100,106] have published the QSPR models for the CMC learned using the most comprehensive databases. In these two last works, authors present comparisons between MLR and ANN models.…”
Section: Cmc Predictionmentioning
confidence: 99%
“…Among all the class of surfactants, anionic surfactants are used in greater volume due to the ease and low cost of manufacture and their wide application in industry and domestic area like detergency, emulsifying agents, solubilizing agents, dispersing agents, fire fighting foams, antistating agents, antifogging agents, adhesives, coatings, pharmaceutical adjuvants etc. (Katritzky et al, 2007;Attwood and Florence, 1983). The most commonly used anionic surfactants are the salts of linear and branched alkyl sulfates and alkane sulfonates, substituted alkane sulfonates, heteroatom containing sulfates and sulfonates (O, N, S), phosphate esters, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used anionic surfactants are the salts of linear and branched alkyl sulfates and alkane sulfonates, substituted alkane sulfonates, heteroatom containing sulfates and sulfonates (O, N, S), phosphate esters, etc. (Katritzky et al, 2007).…”
Section: Introductionmentioning
confidence: 99%